To oversete optegnelser om Struensee og Munter - Glebe-Møller, Jens (Kirkehistoriske Samlinger, 2009)
Two overlooked notes, originally published by the Norwegian historian Ludvig Daae in 1884, are her being reprinted and commented upon. The one testifies to Johann Friedrich Struensee’s well-known irreligiosity or rather agnosticism and the other to his confessor’s, Balthasar Münter’s, pecuniary interest in Struensee’s alleged conversion to the Christian Faith.